Incidence of primary peripheral posterior capsular opacification after cataract surgery and posterior capsular opacification in the patients implanted with foldable intraocular lenses - Joshi, Rajesh Subhash (Nepalese Journal of Ophthalmology, 2018)
Introduction: Preexisting posterior capsular opacification is commonly seen in the developing world due to late presentation of patients for cataract surgery. Patients are implanted with either hydrophilic or hydrophobic IOL. Effect of these IOLs on pre-existing posterior capsular opacification has not yet been reported. Aim: To determine the incidence of peripheral preexisting posterior capsular opacity (PPPCO) in patients undergoing cataract surgery and the rate of posterior capsular opacification (PCO) following implantation of hydrophilic and hydrophobic intraocular lens (IOLs). Study design: Prospective, observational case study Setting: Tertiary eye care center in central India. Methodology: 1400 consecutive patients undergoing phacoemulsification of senile cataract between July 2009 and June 2010 discovered to have PPPCO were included in the analysis. Patients were either implanted with hydrophilic (n= 40) or hydrophobic IOL (n=40). Images of the posterior capsule immediately and 3-years postoperatively were compared. Patients were followed up for development of PCO, visual outcome at 3 years and neodymium: YAG laser posterior capsulotomy (NYLPC) rate. Results: Eighty patients were found to have PPPCO (incidence of 5.7%). 47.5% of PPPCOs were from mature senile cataracts (n = 38), 36.2% were from posterior subcapsular cataracts (n = 29) and 16.2% were from posterior polar cataracts (n = 13). NYLPC was performed in 9 patients receiving hydrophilic (22.5%) and 3 patients receiving hydrophobic IOLs (7.5%; p = 0.12). Average time to NYLPC was 18 months in the hydrophilic and 30 months in the hydrophobic group (p = 0.002). Visual outcome was satisfactory at 3-years of follow-up. Conclusion: PPPCO is a frequent occurrence in mature cataract and there is a higher incidence of PCO in PPPCO patients implanted with hydrophilic IOL than with hydrophobic IOL. Therefore, hydrophobic IOL should be considered for patients discovered to have PPPCO during cataract removal.